HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI DENGAN PERILAKU PENCEGAHAN KEPUTIHAN - Diah Ayu Lestari (Jurnal Ilmiah Citra Kebidanan, 2025)
Background: Women's reproductive health has become a health issue that must be addressed, especially among adolescents. One of the reproductive health problems among adolescents, particularly women, is vaginal discharge. This disorder is the second most common menstrual disorder. Vaginal discharge can often cause discomfort and interfere with daily activities. Objective: To determine the relationship between adolescents' knowledge and attitudes toward vaginal discharge and their preventive behaviors at SMK Pelita Insani. Research Method: This study employed a cross-sectional approach. The data analysis technique used was quantitative descriptive analysis using the chi-square test. The population of this study was 75 female students at SMK Pelita Insani 2025, with a total sampling technique. Research Results: Based on the research results, there was a significant relationship between knowledge and preventive behavior regarding vaginal discharge with a p-value of 0.001. Additionally, there is a significant relationship between attitude and behavior toward preventing vaginal discharge, with a p-value of 0.000 (p < 0.05). Conclusion: There is a significant relationship between knowledge and attitude among female adolescents and behavior toward preventing vaginal discharge at SMK Pelita Insani.